Activation of β-Adrenoceptors by Dobutamine May Induce a Higher Expression of Peroxisome Proliferator-Activated Receptors δ (PPARδ) in Neonatal Rat Cardiomyocytes. (15th May 2012) - Chou, Ming-Ting; Lo, Shih-Hsiang; Cheng, Kai-Chun; Li, Yin-Xiao; Chen, Li-Jen; Cheng, Juei-Tang
Abstract : Recent evidence showed the role of peroxisome proliferator-activated receptors (PPARs) in cardiac function. Cardiac contraction induced by various agents is critical in restoring the activity of peroxisome proliferator-activated receptors δ (PPAR δ ) in cardiac myopathy. Because dobutamine is an agent widely used to treat heart failure in emergency setting, this study is aimed to investigate the change of PPAR δ in response to dobutamine. Neonatal rat cardiomyocytes were used to examine the effects of dobutamine on PPAR δ expression levels and cardiac troponin I (cTnI) phosphorylation via Western blotting analysis. We show that treatment with dobutamine increased PPAR δ expression and cTnI phosphorylation in a time- and dose-dependent manner in neonatal rat cardiomyocytes. These increases were blocked by the antagonist of β 1-adrenoceptors. Also, the action of dobutamine was related to the increase of calcium ions and diminished by chelating intracellular calcium. Additionally, dobutamine-induced action was reduced by the inhibition of downstream messengers involved in this calcium-related pathway. Moreover, deletion of PPAR δ using siRNA generated the reduction of cTnI phosphorylation in cardiomyocytes treated with dobutamine. Thus, we concluded that PPAR δ is increased by dobutamine in cardiac cells.